2007
DOI: 10.1243/13506501jet212
|View full text |Cite
|
Sign up to set email alerts
|

Thermal elastohydrodynamic lubrication characteristics of couple stress fluids in rolling/sliding line contacts

Abstract: A mathematical model is developed to analyse the effect of polymer additives on thermal elastohydrodynamic lubrication (EHL) behaviour under heavily-loaded rolling/sliding line contacts. The lubricant is assumed to be couple stress fluid and a non-dimensional couple stress parameter represents the molecular length of the additives. The Reynolds and mean temperature equations for the couple stress fluid (CSF) are derived using the rheological relationship presented by Stokes. The thermal EHL characteristics com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…The mean temperature T m has been shown in Figures 4 and 5, as a function of n and U . It may be observed that the qualitative behavior of T m versus x is very similar to the temperature profile obtained by Prasad et al (1991), Saini et al (2007). Further, for a fixed value of n, T m increases with U , which indicates that the sliding temperature is higher than that of pure rolling (Ghosh and Hamrock, 1985;Sadeghi and Dow, 1987).…”
Section: Mean Temperature Profilesupporting
confidence: 69%
“…The mean temperature T m has been shown in Figures 4 and 5, as a function of n and U . It may be observed that the qualitative behavior of T m versus x is very similar to the temperature profile obtained by Prasad et al (1991), Saini et al (2007). Further, for a fixed value of n, T m increases with U , which indicates that the sliding temperature is higher than that of pure rolling (Ghosh and Hamrock, 1985;Sadeghi and Dow, 1987).…”
Section: Mean Temperature Profilesupporting
confidence: 69%
“…Accurate empirical formula for the film thickness of EHL elliptical contacts using couple stress lubricant [34] is a good substitute to earlier ones. The influence of couple stress on steady state thermal EHL line contact problem and, later investigation of compressible EHL line contact problem to demonstrate the combined influence of couple stress lubricant with wavy surface roughness on lubrication characteristics are presented in [35,36] respectively. For point contact problem [37] the effects of surface roughness and couple stress lubricant on EHL characteristics using average flow model equation are obtained.…”
Section: Couple Stress Fluidmentioning
confidence: 99%
“…This antisymmetric part of stress tensor manifests itself in the momentum equation by raising its order from two to four. Couple stress theory is used to model many industrial fluid flows, such as lubricants with additives, polymeric fluids with suspensions, colloidal fluids, paints, liquid crystals, magmas, molten alloy, [10][11][12][13][14][15][16] etc. According to Stokes, 9 one could expect couple stresses to appear in noticeable magnitudes in a liquid with very large molecules or with additives.…”
Section: Introductionmentioning
confidence: 99%
“…9 Several researchers have exploited this idea and studied various problems related to industry, physiology, and mechanical engineering. [10][11][12][13][14][15][16] In view of the above discussion, couple stress fluid model is best suited to study the coating of materials with suspended particles or having high molecular weight, for example, ultra-high-molecular-weight polyethylene. Motivated by this fact the aim of this work is to provide the results for this process employing the couple stress fluid constitutive equation.…”
Section: Introductionmentioning
confidence: 99%